Analisis Dampak Metode Diskusi terhadap Pemahaman Konsep Produksi dan Konsumsi di SMA Negeri 1 Bengkayang - Ansela, Ansela; Asriati, Nuraini; Syamsuri, Syamsuri; Matsum, Junaidi H; Syahrudin, Husni (Jurnal Ilmiah Dikdaya, 2025)
Economics learning in secondary schools is often dominated by lecture methods, causing students to become passive and less able to connect concepts with real-life contexts. This condition affects their understanding of basic economic concepts, particularly production and consumption. The purpose of this study was to analyze the effectiveness of the discussion method in improving students’ comprehension of production and consumption concepts at SMA Negeri 1 Bengkayang. This research employed a descriptive approach with 30 purposively selected tenth-grade students as subjects. Data were collected through classroom observations, pre-test and post-test, as well as interviews, and analyzed through data reduction, presentation, and conclusion drawing. The findings revealed a significant improvement in students’ comprehension, as indicated by the increase in the average score from 65 in the pre-test to 82 in the post-test after implementing the discussion method. Moreover, observations and interviews showed that the discussion encouraged students to express their opinions confidently, enhanced collaboration skills, and fostered learning motivation. These results align with constructivist theory, which emphasizes the importance of social interaction and active learning experiences in building understanding. The study concludes that the discussion method contributes not only to the improvement of cognitive learning outcomes but also to the development of students’ affective and social aspects. The practical contribution of this research is to recommend that teachers integrate discussions more frequently in Economics learning, particularly in applied topics, and for schools to provide supporting facilities to ensure effective implementation.